Effect of surgery on tumor progression and malignant degeneration in hemispheric diffuse low-grade astrocytomas - (:unkn) unknown (CHURCHILL LIVINGSTONE, 2002)
The aim of this study is to determine the impact of surgery on tumor progression and malignant degeneration in hemispheric diffuse astrocytoma WHO grade II. Twenty-eight patients who were operated or underwent stereotactic; biopsy for hemispheric diffuse astrocytoma WHO grade II at Marmara University between January 1987 and January 1996, were prospectively reviewed for the presence of recurrence and histopathological dedifferentiation at their fourth years after the initial treatment. Twenty-two patients underwent surgical resection. Of this group, 7 patients had a total, 11 had a subtotal and 4 patients had a partial resection. Six patients underwent stereotactic biopsy. All patients, except for the ones in whom a radiological total surgical removal could be achieved, received postoperative radiotherapy. In the total surgical-removal group only one patient had recurrence, while no upgrade was noted. All of the patients in the partial resection and stereotactic biopsy groups recurred at a higher grade. Our results indicate that both tumor progression and histopathological dedifferentiation were less commonly seen when a total or subtotal resection could be achieved. So, surgery, as radical as possible, should be the choice of treatment in low-grade hemispheric astrocytomas. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: astroctoma; low-grade astrocyoma; surgery; recurrence; radiotherapy; RADIATION-THERAPY; SURVIVAL; ADULTS